23rd Aerospace Sciences Meeting 1985
DOI: 10.2514/6.1985-459
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant Plume Calculations

Abstract: Tilts is a preprint of a paper intended Tor publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with Hie un derstanding that it will not be cited or reproduced without the permission ef the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Additionally, for the cases with moisture, the effects of a radiation parameterization are also evaluated. Although previous studies (Penner et al, 1986) found that plume rise is very sensitive to the fuel burned (and, therefore, the amount of energy released), changes in fuel loading are not considered here. Our simulations all employ a homogeneous wildland fuel bed of about 1.3 g cm -2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, for the cases with moisture, the effects of a radiation parameterization are also evaluated. Although previous studies (Penner et al, 1986) found that plume rise is very sensitive to the fuel burned (and, therefore, the amount of energy released), changes in fuel loading are not considered here. Our simulations all employ a homogeneous wildland fuel bed of about 1.3 g cm -2 .…”
Section: Discussionmentioning
confidence: 99%
“…12, where a metric for lofting (the height above which 50% of smoke is lifted) is plotted for each case and fire size. We compare our final vertical smoke profiles with those of Penner et al (1986) and Reisner et al (2018) in Fig. 13.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations